Combined Non‐invasive PIXE/PIGE Analyses of Mammoth Ivory from Aurignacian Archaeological Sites. Issue 25 (25th April 2018) - Reiche, Ina; Heckel, Claire; Müller, Katharina; Jöris, Olaf; Matthies, Tim; Conard, Nicholas J.; Floss, Harald; White, Randall
Abstract: Among the earliest Homo sapiens societies in Eurasia, the Aurignacian phase of the Early Upper Paleolithic, approximately 40 000–30 000 years ago, mammoth ivory assumed great social and economic significance, and was used to create hundreds of personal ornaments as well as the earliest known works of three‐dimensional figurative art in the world. This paper reports on the results of micro‐PIXE/PIGE analyses of mammoth‐ivory artifacts and debris from five major sites of Aurignacian ivory use. Patterns of variable fluorine content indicate regionally distinctive strategies of ivory procurement that correspond to apparent differences in human–mammoth interactions. Preserved trace elements (Br, Sr, Zn) indicate that differences at the regional level are applicable to sourcing Paleolithic ivory at the regional scale. Abstract : Ivory procurement in Paleolithic societies : Non‐invasive micro‐PIXE/PIGE analyses of Paleolithic ivory coupled with archaeological data may provide added support to studies of human behavior. The assessment of ivory preservation and differentiation of ivory source at the regional level provide new insights into the behaviors of Europe's earliest Homo sapiens societies, including regionally specific patterns in the procurement and use of mammoth ivory.